Early enamel lesion part II. Histo-morphology and prevention - Kudiyirickal, Marina George; Koberová Ivančaková, Romana (Acta Medica, 2008)
There has been a paradigm shift from Black's 'extension for prevention' to a minimal intervention approach in the recent time. The most important aspect in diagnosis of earliest stages of enamel demineralization involves accurate and reliable detection of such lesions. The newer diagnostic aids would enable the dentist to detect and diagnose early enamel lesions and direct appropriate preventive measures to promote remineralization and conservation of the tooth substance. A high level of caries experience necessitates preventive strategies which are more cost effective than surgical intervention and restorative procedures.
Keywords: demineralizace zubů; zubní sklovina; lidé; Dental Caries; zubní kaz; Tooth Remineralization; Dental Enamel; Tooth Demineralization; remineralizace zubů; Humans